The Chinese herbal formula QiangGuYin regulates the Wnt/β-catenin pathway in osteoblasts by intervening in the expression of miRNAs derived from osteoclast exosomes - Binbin Tang; Yifeng Yuan; Shen Wang; Shaohua Li; Shifa Kang; Caijian He; Hang Zhou; Mouhao Fang; Tianpeng Chen; Kang Liu; Xiaolin Shi (Elsevier, 2022)
Objective: To explore the effects of a TCM compound QiangGuYin (QGY) regulating osteoclast derived exosomal miRNAs on the Wnt/β-catenin pathway in osteoclast and osteoblasts. Methods: QGY containing serum was prepared to construct osteogenic and osteoclastic differentiation models. Setting up a non-medicated and a medicated serum group with intervention on osteoclast differentiation after extraction of exosomes, the exosome morphology, quantity as well as secretion were examined, while miRNA sequencing of exosomes from the groups was performed. Then, observing the expression of Runx2, OPN, OCN by qRT-PCR and Western blot after adding the groups of exosomes. Finally, RAW264.7 and BM-MSCs were intervened with medicated serum to observe different effects on the expression of β-catenin. Results: The morphology, quantity and secretion of exosomes were not affected by the presence of medicated versus non medicated serum, and exosomes from the two groups appeared identical by electron microscopy; the expression of Runx2, OPN, OCN, β-catenin and miR-27b-3p were markedly increased in osteoblast after intervening by medicated-serum exosomes. Conclusion: QGY can inhibit osteoclast differentiation and decrease the inhibitory effect of exosomes on osteoblast differentiation, and the mechanism may be through affecting miR-27b-3p in exosomes and interfering with the Wnt/β-catenin pathway, affecting osteoblast differentiation.